Analysis of the Success Rate of Paid Click Advertising and Risk Perception on Behavior and Purchases Impulsivity in Online Shopping - ‎ , Pristiyono; Nasution, Ade Parlaungan; ‎ , Abd. Halim; Febriani, Budi; Arjuna, Syukron; ‎ , Mahirun; ‎ , Sriono (KnE Social Sciences, 2024)
This study aimed to analyze the impact of paid click advertising on online purchasing behavior, assess the significant influence of perceived risk on online purchasing behavior, and investigate the indirect effect of paid click advertising and perceived risk on online impulse purchases, with a subsequent examination of how online impulse purchases directly impact consumer emotional intelligence. The population in this study are all people who have recorded experience using QRIS payments in the city of Rantauprapat as a payment method and the sample size used is 150 respondents. The data tested model uses the SEM-PLS (Partial Least Square) structural equation technique using Smart-PLS 4.0 software, within the framework of quantitative descriptive research methodology.. Based on the results of research and discussion, the findings of this study are as follows: first, The majority of respondents reported experiencing impulsive buying, primarily influenced by online advertisements viewed through smartphone applications, with 58 individuals (38.7%) attributing their online shopping behavior to this factor. Second, the results of the study partially show that paid click advertising and perceived risk have a positive and significant effect on online purchasing behavior and impulsive buying online. Third, partially that online purchasing behavior has a positive and significant effect on impulsive buying online. Finally, partially impulsive buying online has a positive and significant effect on emotional intelligence. Keywords: paid click advertising, risk perception, online purchasing behavior, online impulsive buying, consumer emotional intelligence